2014
DOI: 10.1111/jeb.12345
|View full text |Cite
|
Sign up to set email alerts
|

The role of sex chromosomes in sexual dimorphism: discordance between molecular and phenotypic data

Abstract: In addition to initial sex determination, genes on the sex chromosomes are theorized to play a particularly important role in phenotypic differences between males and females. Sex chromosomes in many species display molecular signatures consistent with these theoretical predictions, particularly through sex-specific gene expression. However, the phenotypic implications of this molecular signature are unresolved, and the role of the sex chromosomes in quantitative genetic studies of phenotypic sex differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 112 publications
3
92
0
Order By: Relevance
“…Sexual dimorphism in fish not only includes size dimorphism, shape dimorphism and color dimorphism, but also comprises sexual differences in physiology and behavior [43,44]. Long-term field surveys and aquaculture practices have observed significant size dimorphism between male and female individuals in more than 20 fish species.…”
Section: Sexual Dimorphism and Its Genetic Basis In Fish 21 Diversitmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual dimorphism in fish not only includes size dimorphism, shape dimorphism and color dimorphism, but also comprises sexual differences in physiology and behavior [43,44]. Long-term field surveys and aquaculture practices have observed significant size dimorphism between male and female individuals in more than 20 fish species.…”
Section: Sexual Dimorphism and Its Genetic Basis In Fish 21 Diversitmentioning
confidence: 99%
“…Theoretically, sex chromosomes and the genes located on them may play critical roles in sexual dimorphism [77,78]. In some cases, however, sex chromosomes are not the leader of sexual dimorphism, because quantitative genetic studies have observed discordance between sex chromosomes and phenotypic data [79]. Genetic architecture of threespine stickleback fish (Gasterosteus aculeatus) is very similar between males and females, but many traits show significant sexual difference, suggesting that genetic constraints for evolution of sex dimorphism might not be so severe and absolute as generally thought [80].…”
Section: Genetic Basis Of Sexual Dimorphism In Fishmentioning
confidence: 99%
“…The low X coverage would be particularly unfortunate if there is a large X effect, that is if the X is disproportionately influencing reproductive isolation (Presgraves, 2008) or genes under sexual selection (Qvarnstrom and Bailey, 2009;Dean and Mank, 2014), which may have further hindered our ability to detect segregating genetic variation for these traits.…”
Section: Comparison Between Populationsmentioning
confidence: 99%
“…All this theory predicts that although the sex chromosomes generally represent a small proportion of the genome, they should play a disproportionately large role in sexual conflict, sexual dimorphism, and sexual selection. There is substantial empirical evidence supporting at least some of this theory (Table 1, and references therein), although there remains something of a disconnect between molecular genetic and phenotypic findings (Dean and Mank 2014).…”
mentioning
confidence: 99%